2021
DOI: 10.2340/16501977-2748
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and psychological effects of a multimodal day-care rehabilitation program for persons with Huntington's disease

Abstract: Objective To determine whether the psychological benefits of intense, inpatient, multimodal rehabilitation for persons with Huntington’s disease (HD), as found in earlier studies, also apply in a shorter, day-care setting. Design Prospective, non-randomized cohort study. Subjects Twenty patients attending a group-based 8-week (3 days/week) rehabilitation programme aimed at persons in early stages of HD. Methods An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Five intervention studies were performed that included (HR)QoL as a primary or main outcome measure [ 18 , 27 , 28 , 46 , 47 ]. Three out of five studies reported a beneficial intervention effect on (HR)QoL [ 27 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five intervention studies were performed that included (HR)QoL as a primary or main outcome measure [ 18 , 27 , 28 , 46 , 47 ]. Three out of five studies reported a beneficial intervention effect on (HR)QoL [ 27 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…A significant and positive effect on HRQoL was also found for a multimodal rehabilitation program in 20 mHDGECs [ 47 ]. The program consisted of 25 days of rehabilitation spread across 8 weeks, and included information and education sessions, counseling, and physical training in a group setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only five intervention studies have been conducted with (HR)QoL as a primary outcome measure. Three of these studies reported beneficial effects for (HR) QoL of a multidisciplinary rehabilitation program [27,47] and a respiratory muscle training [46] in mHDGECs. The multidisciplinary rehabilitation programs that were carried out in two of these studies targeted some of the dynamic factors mentioned above, including physical and cognitive functioning [27,47], psychological functioning [47], and guidance on social support [47].…”
Section: Discussionmentioning
confidence: 99%
“…Five intervention studies were performed that included (HR) QoL as a primary or main outcome measure [18,27,28,46,47]. Three out of five studies reported a beneficial intervention effect on (HR)QoL [27,46,47].…”
Section: Intervention Effects On (Hr)qolmentioning
confidence: 99%